METAPHORS IN MICHAEL BUBLE’S FIFTH STUDIO ALBUM “CALL ME IRRESPONSIBLE” - Ashshalihah, Nuraulia; Halim, Abd; Mustikawati, Yunitari (Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This research discusses metaphors used in Michael Buble’s fifth studio album “Call Me Irresponsible”. This research examines the types of metaphors in Michael Buble’s fifth studio album “Call Me Irresponsible” and the meaning of each metaphors in the album. The researcher uses the descriptive qualitative method to analyze the objectives of the research. The results of this research indicate that there are 26 data found in the form of lyrics containing metaphors. Among them are 12 structural metaphors, 9 orientational metaphors, and 5 ontological metaphors which consist of personification metaphor. In addition,the meaning that contained in each of metaphors depends on the type of metaphor used which are: 1) structural metaphors happen when a concept is expressed in terms of other defined concepts, 2) orientational metaphor can highlight how cultural representations of physical and emotional experience such as “Happy is up, sad is down.”, and 3) ontological metaphors happen when we see events, activities, feelings, and ideas as beings and things.Keywords : Structural Metaphors, Orientational Metaphors, Ontological Metaphors, Song, Call Me Irresponsible Album